TGF-β trap of AdAPT-001 turns up the heat on tumors and turns down checkpoint blocker resistance - Anthony Conley; Jeannie Williams; Bryan Oronsky; Tony R Reid; Scott Caroen (Journal for ImmunoTherapy of Cancer)
At the ASCO 2024 meeting, Anthony P Conley, coauthor on this editorial, presented promising data from the phase 1/2 clinical trial called BETA PRIME (ClinicalTrials.gov NCT04673942) with AdAPT-001 plus a checkpoint inhibitor (CI). All participants gave informed consent to participate in BETA PRIME before taking part. AdAPT-001 is an oncolytic adenovirus that expresses a transforming growth factor beta (TGF-β) trap to neutralize active TGF-β. This editorial proposes that the TGF-β trap of AdAPT-001 reverses the immunosuppressive environment of tumor cells, and thus makes these tumors susceptible to CIs like the anti-PD-1 agent, nivolumab, and potentially other therapies as well.